Effects of Wheat and Fish Trade Restriction Policies on Households’ Vulnerability to Poverty in Nigeria (2019)
Against the expected trade liberalization policies as enunciated under the World Trade Organization (WTO) agreement, Nigeria currently uses trade restriction policies through tariffs and quotas to protect local producers and ensure self-sufficiency in staple food especially wheat and fish, which constitute 56% of annual food import. However, the general equilibrium effects of restrictive policy instruments are yet to be fully understood especially for the poor and the vulnerable. Living Standard (HNLSS) survey data for 2009/2010 and the NISER’s 2011 Social Accounting Matrix (SAM) were used. An 80% wheat and 50% fish tariff increase as currently implemented in Nigeria were used for the simulations. Data were analyzed using computable general equilibrium (CGE) technique and Vulnerability To Poverty (VTP) measure. Prior to policy simulations, vulnerable rural and urban households in NW had the highest observed poverty (68.2% and 71.2%) while, while the rural and urban households in the south-south zone had the least (53.0% and 45.5%) respectively. The expected poverty was highest in simulation three across vulnerable and non-vulnerable households. Consequently, the ratio of expected to observed poverty indicates that vulnerable rural and urban households have the highest likelihood of sinking deeper into poverty particularly with the combined policies in simulation three. It is therefore recommended that government should strengthen domestic production of food import substitutes backed with strong value addition.